Preparation method of rare earth modified aluminum phosphate-based high-temperature adhesive

Through the preparation method of rare earth modified aluminum phosphate-based high-temperature adhesive, the problems of low bonding strength and poor thermal expansion at high temperatures are solved, and high-strength stable connections and bonding are achieved in high temperature environments. The strength is increased to more than 30MPa, which significantly improves the bonding effect of alumina ceramics.

CN119193008APending Publication Date: 2024-12-27CIVIL AVIATION UNIV OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411547548.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing aluminum phosphate-based high-temperature adhesives have low bonding strength to alumina ceramics at high temperatures, and are highly brittle, with a large difference in thermal expansion coefficient and the bonded substance, making it difficult to meet the connection needs in high temperature environments.

Method used

The preparation method of rare earth modified aluminum phosphate-based high-temperature adhesive is adopted. By ball milling silicon powder and boron carbide, rare earth oxide and aluminum hydroxide are added to the dilute phosphoric acid solution, and after multi-stage stirring and heating treatment, the rare earth modification is formed. Aluminum phosphate-based high-temperature adhesive enhances its bonding strength and thermal expansion properties.

Benefits of technology

Provides a bonding strength of no less than 6MPa within the temperature range of 900 to 1300°C, and the bonding strength of no less than 30MPa within the temperature range of 1100 to 1300°C, forming stable connections without cracking problems, significantly improving bonding in high temperature environments Connector performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119193008A_ABST
    Figure CN119193008A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a rare earth modified aluminum phosphate-based high-temperature adhesive. The method comprises the following steps: mixing boron carbide and silicon powder to prepare an inorganic filler; mixing rare earth oxide, aluminum hydroxide and dilute phosphoric acid according to a certain proportion, and preparing macromolecular phosphate gum base liquid based on hydrothermal reaction; and finally, fully mixing the adhesive base solution with the inorganic filler to prepare the rare earth modified aluminum phosphate-based high-temperature adhesive. The high-temperature adhesive disclosed by the invention is based on the aluminum phosphate adhesive base solution doped with the rare earth element, and the aim of changing the adhesive property of the high-temperature adhesive is fulfilled in a manner of regulating and controlling the proportion of the rare earth element, the aluminum element and the phosphorus element. The high-temperature adhesive has the following effects that a stable and compact complex-phase structure of rare earth phosphate and aluminum phosphate is generated in the high-temperature adhesive due to doping of rare earth elements; the rare earth phosphate not only can reinforce the aluminum phosphate matrix, but also can improve the thermal expansion property of the adhesive matrix, so that the high-temperature adhesive shows excellent adhesive property on aluminum oxide. And after the treatment at the calcining temperature of 1300 DEG C, the adhesive can provide the bonding strength of not less than 30 MPa for the bonding of the aluminum oxide ceramic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesive material preparation, and in particular relates to a method for preparing a high-temperature adhesive suitable for connecting, installing and repairing alumina ceramics. Background Art

[0002] Alumina has excellent high temperature stability and high mechanical strength, so it has been widely used in many fields. In the alumina crystal, oxygen atoms and aluminum atoms are combined by covalent bonds, so the alumina crystal has extremely high hardness, which also makes it have stable chemical properties at high temperatures and can effectively resist the erosion of acids, alkalis, slags, metal solutions, etc. In addition, alumina is also widely used in ceramic manufacturing. Due to its high temperature resistance and wear resistance, it is particularly suitable for harsh environments, such as ceramic protection tubes, wear-resistant alumina ceramic lining bricks and other refractory materials, ceramic seals, alumina ceramic bearings and other mechanical equipment, alumina ceramic substrates, alumina ceramic electrical insulation parts and other electronic equipment. In order to meet the application requirements of the above extreme situations, an effective and convenient method for connecting alumina ceramics is usually required. Today's main connection methods include mechanical connection, metal brazing, diffusion connection, etc., and these connections cannot fully meet the requirements of effective and convenient connection. In comparison, phosphate adhesive connection can better meet the above requirements, among which aluminum phosphate-based adhesives are more widely used.

[0003] With the advancement of science and technology, the performance of aluminum phosphate-based high-temperature adhesives has been significantly improved, and they can withstand higher temperatures and are increasingly widely used. This type of inorganic adhesive is favored for its excellent high-temperature resistance and flame retardant properties. The heat-resistant temperature can reach 1300-1600℃. It can be used as the basis of ablative materials to replace traditional organic compounds and has high bonding strength. Various cementitious materials based on aluminum phosphate-based high-temperature adhesives not only show good plasticity, room-temperature curing and low relative density, but also have the high-temperature vitrification characteristics of ceramic materials, as well as the heat resistance and impact resistance of refractory materials. During the application process, aluminum phosphate-based high-temperature adhesives need to interact with other inorganic fillers to form the required materials, and the role of fillers will vary with changes in temperature. Fillers can not only enhance the cohesion of adhesives, reduce shrinkage, prevent fractures and improve heat resistance, but also increase bonding strength. In addition, fillers also enable adhesives to have functions such as electrical conductivity, thermal conductivity, magnetic conductivity, as well as corrosion resistance, heat resistance, wear resistance and coloring.

[0004] However, aluminum phosphate-based high-temperature adhesives are extremely brittle, and have a large difference in thermal expansion coefficient with the bonded phase. Their ability to withstand impact loads is not high, which often results in poor bonding strength to simple planes. Since the thermal expansion coefficient of aluminum phosphate-based high-temperature adhesives is significantly lower than that of alumina ceramics, the bonding strength of the adhesive to alumina ceramics at high temperatures is low, usually not higher than 2MPa. The addition of rare earth elements can regulate the thermal expansion coefficient to a certain extent, but there are few reports on rare earth-modified aluminum phosphate-based high-temperature resistant adhesives. Therefore, it is of great significance to develop rare earth-doped and modified aluminum phosphate-based high-temperature adhesives. Summary of the invention

[0005] In order to solve the above problems, the purpose of the present invention is to provide a method for preparing a rare earth modified aluminum phosphate based high temperature resistant adhesive.

[0006] In order to achieve the above object, the present invention provides a method for preparing a rare earth modified aluminum phosphate based high temperature adhesive, comprising the following steps performed in sequence:

[0007] 1. A method for preparing a rare earth modified aluminum phosphate based high temperature adhesive, characterized in that: the preparation method comprises the following steps performed in sequence:

[0008] (1) Silicon powder and boron carbide are mixed in a mass ratio of 6.5-7.4:2.6-3.5, placed in a ball mill, and milled at 275-335 r / min for 7-10 hours, then taken out, dried and ground, and used as an inorganic filler for high-temperature adhesives;

[0009] (2) Dilute the concentrated phosphoric acid with a concentration of 85wt.% to 60-65wt.%, then place it in a water bath heating pot equipped with a cooling reflux device, heat it to 70-80°C, and then quickly add rare earth oxides and aluminum hydroxide to the dilute phosphoric acid solution at a molar ratio of rare earth element, aluminum element and phosphorus element of 0.05-0.25:0.75-0.95:0.9-1.1 under high-speed mechanical stirring (450-650r / min). Then, keep the water bath heating temperature at 80-85°C, stir at a speed of 750-850r / min for 1.5-2.5h, and then stir at 350-450r / min for 7-9h;

[0010] (3) The set temperature of the water bath heating pot in step (2) is lowered to 55-65°C. After the temperature drops to the range, the mixed inorganic filler obtained in step (1) is added to the mortar obtained in step (2) at a solid-liquid mass ratio of 1:4-6, and the mixture is stirred alternately at a speed of 450-750 r / min for 8-12 hours to prepare a rare earth modified aluminum phosphate-based high-temperature adhesive.

[0011] 2. Preferably, in step (1), the elemental silicon powder is a nanometer-scale regulator with a particle size of 0.5-1 μm and a purity higher than 99%. Boron carbide is a non-standard mineral with a particle size of 8-10 μm and a purity higher than 99%.

[0012] 3. Preferably, the concentrated phosphoric acid in step (2) is analytical grade with a purity higher than 98%; the aluminum hydroxide is sieved through 300 mesh with a purity higher than 95%.

[0013] 4. Preferably, the rare earth oxide in step (2) comprises samarium oxide (Sm 2 O 3 ), neodymium oxide (Nd 2 O 3 ), cerium oxide (CeO 2 ), lanthanum oxide (La 2 O 3 ), europium oxide (Eu 2 O 3 ), etc., all of which were sieved through 300 meshes, and the purity was higher than 99%.

[0014] 5. Preferably, the stirring in different temperature sections or time periods in step (2) needs to be carried out under a cooling reflux device.

[0015] 6. Preferably, in step (3), fast and slow alternating stirring is performed within the speed range of 450-750 r / min, generally stirring for 2-3 h within the speed range of 650-750 r / min, then stirring for 3-4 h within the speed range of 550-650 r / min, and finally stirring for 3-5 h within the speed range of 450-550 r / min.

[0016] The preparation method of the rare earth modified aluminum phosphate-based high-temperature adhesive provided by the present invention has the following beneficial effects:

[0017] 1. After high temperature treatment, the high temperature adhesive can provide a bonding strength of not less than 6MPa in the temperature range of 900-1300°C, and the bonding strength in the range of 1100-1300°C is higher than 30MPa.

[0018] 2. After being treated at different temperatures, this high temperature adhesive can form a stable connection with the surface of alumina ceramics without cracking problems, and the interface connection effect is good.

[0019] 3. After the adhesive is calcined at 1300℃, the main components are transformed into various ceramic phase substances such as aluminum phosphate and rare earth phosphate. These ceramic phase substances are extremely conducive to forming stable adhesive joints in high temperature environments due to their high temperature resistance and excellent mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 11 is a shear strength curve of an alumina ceramic bonded part bonded by the samarium oxide modified aluminum phosphate based high temperature adhesive prepared in Example 1 tested at room temperature after being treated at different temperatures;

[0021] Figure 2 The shear strength curves of the alumina ceramic bonded parts bonded by the neodymium oxide modified aluminum phosphate based high temperature adhesive prepared in Example 2 tested at room temperature after being treated at different temperatures;

[0022] Figure 3 This is a shear strength curve of the alumina ceramic bonded part bonded by the cerium oxide modified aluminum phosphate based high temperature adhesive prepared in Example 3 tested at room temperature after being treated at different temperatures;

[0023] Figure 4 is the XRD spectrum of the samarium oxide modified aluminum phosphate-based high-temperature adhesive prepared in Example 1 after being treated at 1300° C.;

[0024] Figure 5 is the XRD spectrum of the neodymium oxide-modified aluminum phosphate-based high-temperature adhesive prepared in Example 2 after being treated at 1300° C.;

[0025] Figure 6 is the XRD spectrum of the cerium oxide modified aluminum phosphate-based high-temperature adhesive prepared in Example 3 after being treated at 1300° C.;

[0026] Figure 7 is a SEM photograph of the bonding surface of the alumina ceramic bonding part bonded by the samarium oxide modified aluminum phosphate based high temperature adhesive prepared in Example 1 after being treated at 1300°C;

[0027] Figure 8 This is a SEM photograph of the bonding surface of the alumina ceramic bonding part bonded by the neodymium oxide-modified aluminum phosphate-based high-temperature adhesive prepared in Example 2 after being treated at 1300° C.;

[0028] Fig. 9 This is a SEM photograph of the bonding surface of the alumina ceramic bonding part bonded by the cerium oxide-modified aluminum phosphate-based high-temperature adhesive prepared in Example 3 after being treated at 1300° C.; DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The present invention provides a technical solution: a method for preparing a rare earth modified aluminum phosphate-based high-temperature adhesive, which specifically comprises the following steps:

[0031] Embodiment 1:

[0032] (1) Silicon powder and boron carbide are mixed in a mass ratio of 7:3, placed in a ball mill, and milled at 320 r / min for 8 h. The mixture is taken out and dried and ground to be used as an inorganic filler for high-temperature adhesives.

[0033] (2) Dilute concentrated phosphoric acid with a mass fraction of 85wt.% to 60wt.%, heat it to 70°C in a water bath heating pot equipped with a cooling reflux device, and then quickly add samarium oxide and aluminum hydroxide to the dilute phosphoric acid solution at a molar ratio of samarium, aluminum and phosphorus of 0.25:0.75:0.9 under high-speed mechanical stirring at 450r / min. Then, keep the water bath heating temperature at 80°C, stir at 750r / min for 2.5h, and then stir at 450r / min for 7h;

[0034] (3) The set temperature of the water bath heating pot in step (2) is lowered to 55°C. After the temperature drops to the range, the mixed modified filler obtained in step (1) is added to the light yellow slurry obtained in step (2) at a solid-liquid mass ratio of 1:5, and stirred at a speed of 750 r / min for 2 h, and then stirred at a speed of 650 r / min for 3 h, and finally stirred at a speed of 550 r / min for 3 h, thereby preparing a samarium oxide modified aluminum phosphate-based high-temperature adhesive.

[0035] Embodiment 2:

[0036] (1) Silicon powder and boron carbide are mixed in a mass ratio of 6.5:3.5, placed in a ball mill, and milled at 335 r / min for 9 h. Then, the mixture is taken out, dried, and ground into fine powder, and the mixture can be used as a modified filler for a high-temperature adhesive.

[0037] (2) Dilute concentrated phosphoric acid with a mass fraction of 85wt.% to 63wt.%, heat it to 75°C in a water bath heating pot equipped with a cooling reflux device, and then quickly add neodymium oxide and aluminum hydroxide to the dilute phosphoric acid solution at a molar ratio of neodymium, aluminum and phosphorus of 0.20:0.80:1.1 under high-speed mechanical stirring at 550r / min. Then, keep the water bath heating temperature at 80°C, stir at 800r / min for 1.75h, and then stir at 400r / min for 8h;

[0038] (3) The set temperature of the water bath heating pot in step (2) is lowered to 60°C. After the temperature drops to the range, the mixed modified filler obtained in step (1) is added to the lavender slurry obtained in step (2) at a solid-liquid mass ratio of 1:4, and stirred at a speed range of 700 r / min for 2.5 h, then stirred at a speed range of 600 r / min for 4 h, and finally stirred at a speed range of 500 r / min for 4 h, thereby preparing a neodymium oxide-modified aluminum phosphate-based high-temperature adhesive.

[0039] Embodiment three:

[0040] (1) Silicon powder and boron carbide are mixed in a mass ratio of 7.4:2.6, placed in a ball mill, and milled at 275 r / min for 10 h. Then, the mixture is taken out, dried, and ground into fine powder, and the mixture can be used as a modified filler for a high-temperature adhesive.

[0041] (2) Dilute concentrated phosphoric acid with a mass fraction of 85wt.% to 65wt.%, heat it to 80°C in a water bath heating pot equipped with a cooling reflux device, and then quickly add cerium oxide and aluminum hydroxide to the dilute phosphoric acid solution at a molar ratio of cerium, aluminum and phosphorus of 0.05:0.95:1 under high-speed mechanical stirring at 650r / min. Then, keep the water bath heating temperature at 85°C, stir at 850r / min for 1.5h, and then stir at 350r / min for 9h;

[0042] (3) The set temperature of the water bath heating pot in step (2) is lowered to 65°C. After the temperature drops to the range, the mixed modified filler obtained in step (1) is added to the light yellow slurry obtained in step (2) at a solid-liquid mass ratio of 1:6, and stirred at a speed of 650 r / min for 3 h, then stirred at a speed of 550 r / min for 4 h, and finally stirred at a speed of 450 r / min for 5 h, thereby preparing a cerium oxide modified aluminum phosphate-based high-temperature adhesive.

[0043] In the rare earth modified aluminum phosphate based high temperature adhesive prepared by the method of the present invention, the main adhesive phase is a macromolecular phosphate emulsion prepared by reacting dilute phosphoric acid with aluminum hydroxide and rare earth oxides. Silicon powder can improve the viscosity of the slurry and play a role in regulating viscosity. It can also be oxidized at high temperature to generate silicon dioxide to improve the density of the adhesive matrix structure. In this invention, boron carbide can be oxidized in a high temperature environment for volume compensation, or it can react with aluminum oxide at high temperature to generate aluminum borate to improve the mechanical properties of the adhesive itself. At high temperature, the macromolecular phosphate decomposes to generate aluminum phosphate with high temperature adhesion and needle-shaped rare earth phosphate, and the two are distributed alternately to form a high-strength composite structure. In addition, the thermal expansion coefficient of rare earth phosphate is slightly higher than that of aluminum phosphate, which can improve the thermal expansion of the adhesive matrix to a certain extent and better match with aluminum oxide.

[0044] In order to verify the bonding effect of the rare earth modified aluminum phosphate-based high temperature adhesive provided in the above embodiments, the inventors carried out the following verification experiments on the samarium oxide modified aluminum phosphate-based high temperature adhesive prepared in Embodiment 1, the neodymium oxide modified aluminum phosphate-based high temperature adhesive prepared in Embodiment 2, and the cerium oxide modified aluminum phosphate-based high temperature adhesive prepared in Embodiment 3. The experimental steps are as follows:

[0045] (1) Lay multiple alumina ceramic substrates (40×10×5 mm) that have been polished, cleaned, and dried flat on a smooth, flawless glass plate with the bonding surface facing upward;

[0046] (2) Using a scraper, the high-temperature adhesive obtained in the three embodiments is applied to the bonding surface of the alumina ceramic substrate, and the bonding area is controlled to be 15×10 mm. Then, a coater is used to control the thickness of the high-temperature adhesive on each bonding surface to be 200 μm;

[0047] (3) Place the two substrates on their bonding surfaces and press them tightly with your hands. After 10 seconds, place them at room temperature for curing. To ensure stability during the curing process, use a heavy object to apply pressure at the center of the bonding surface.

[0048] (4) The cured bonded parts are placed in a muffle furnace and calcined at the treatment temperatures of 700°C, 900°C, 1100°C, and 1300°C, respectively, and calcined for 1 hour at each temperature.

[0049] (5) Room temperature shear test: The approximate shear strength of the bonded parts of different embodiments after being treated at different temperatures was tested using a CSS-44001 universal testing machine to evaluate the bonding performance of the high temperature adhesive. Figure 1 , Figure 2 , Figure 3 shown.

[0050] Depend on Figure 1 , Figure 2 , Figure 3 It can be seen that the three adhesives prepared in the embodiment can provide alumina ceramics with a bonding strength of more than 6MPa after calcination at 700-1300°C; the strength in the range of 700-1100°C is maintained at about 6-13MPa; after treatment at 1300°C, the strength increases sharply and can be maintained at 30-50MPa, which is much greater than the unmodified aluminum phosphate adhesive.

[0051] (6) Analysis of high temperature adhesive composition: The high temperature adhesives prepared in the three embodiments were treated at 1300°C and then ground into powder. The composition of the high temperature adhesive was then analyzed using a D / Max 2500v / PC XRD tester. Their XRD patterns are shown below: Figure 4 , Figure 5 , Figure 6 shown.

[0052] Depend on Figure 4 , Figure 5 , Figure 6 It can be seen that after treatment at 1300°C, Examples 1, 2, and 3 all produced relatively obvious aluminum phosphate (AlPO 4 ).from Figure 4 It can be seen that the samarium oxide in Example 1 has been completely reacted, and the rare earth oxides have been converted into samarium phosphate (SmPO 4 ), similarly, the neodymium oxide in Example 2 reacts to generate neodymium phosphate (NdPO 4 ), while the Ce element was not detected in Example 3, which is presumed to be of low content and the peak formed is not obvious. The Si in the adhesive is oxidized to SiO by the oxygen-containing groups inside the adhesive at high temperature. 2 , which can react with Al at a high temperature of 1300℃ 2 O 3 The reaction generates high temperature resistant phase mullite. The formation of this high temperature resistant phase is the main reason why this high temperature adhesive has excellent bonding properties. In addition, the adhesive also generates a large amount of Al 5 BO 9 Therefore, in summary, the adhesive of Example 3 not only has a relatively short curing time, but also can generate a high temperature resistant phase at high temperature to improve the bonding strength of the adhesive.

[0053] (7) Analysis of bonding surface morphology: The bonded parts treated at 1300°C were made into SEM test specimens, and the microscopic morphology of the cross section of the bonded parts was observed using a Nanosem430 scanning electron microscope analyzer. Figure 7 , Figure 8 , Fig. 9 As shown; the two sides of the figure are alumina ceramic substrates, and the middle is a high-temperature glue layer.

[0054] Depend on Figure 7 , Figure 8 , Fig. 9 It can be seen that the adhesive layer after treatment at 1300℃ is fuller and denser, without any large cracks, the adhesive and ceramic are well connected, the interface is continuous, and the bonding effect is excellent.

Claims

1. A method for preparing a rare earth modified aluminum phosphate-based high temperature adhesive, characterized in that: The preparation method comprises the following steps performed in sequence: (1) Silicon powder and boron carbide are mixed in a mass ratio of 6.5-7.4:2.6-3.5, placed in a ball mill, and milled at 275-335 r / min for 7-10 hours, then taken out, dried and ground, and used as an inorganic filler for high-temperature adhesives; (2) Dilute the concentrated phosphoric acid with a concentration of 85wt.% to 60-65wt.%, then place it in a water bath heating pot equipped with a cooling reflux device, heat it to 70-80°C, and then quickly add rare earth oxides and aluminum hydroxide to the dilute phosphoric acid solution at a molar ratio of rare earth element, aluminum element and phosphorus element of 0.05-0.25:0.75-0.95:0.9-1.1 under high-speed mechanical stirring (450-650r / min). Then, keep the water bath heating temperature at 80-85°C, stir at a speed of 750-850r / min for 1.5-2.5h, and then stir at 350-450r / min for 7-9h; (3) The set temperature of the water bath heating pot in step (2) is lowered to 55-65°C. After the temperature drops to the range, the mixed inorganic filler obtained in step (1) is added to the mortar obtained in step (2) at a solid-liquid mass ratio of 1:4-6, and the mixture is stirred alternately at a speed of 450-750 r / min for 8-12 hours to prepare a rare earth modified aluminum phosphate-based high-temperature adhesive.

2. A method for preparing a rare earth modified aluminum phosphate based high temperature adhesive according to claim 1, characterized in that: In the step (1), the silicon powder is a nanometer-level regulator, with a particle size of 0.5-1 μm and a purity higher than 99%. Boron carbide is a non-standard mineral, with a particle size of 8-10 μm and a purity higher than 99%.

3. A method for preparing a rare earth modified aluminum phosphate based high temperature adhesive according to claim 1, characterized in that: The concentrated phosphoric acid in step (2) is analytical grade with a purity higher than 98%; the aluminum hydroxide is sieved through 300 meshes with a purity higher than 95%.

4. A method for preparing a rare earth modified aluminum phosphate based high temperature adhesive according to claim 1, characterized in that: The rare earth oxides in step (2) include samarium oxide (Sm2O3), neodymium oxide (Nd2O3), cerium oxide (CeO2), lanthanum oxide (La2O3), europium oxide (Eu2O3), etc., all of which are sieved through 300 mesh and have a purity higher than 99%.

5. A method for preparing a rare earth modified aluminum phosphate based high temperature adhesive according to claim 1, characterized in that: The stirring at different temperature sections or time periods in step (2) needs to be carried out under a cooling reflux device.

6. A method for preparing a rare earth modified aluminum phosphate based high temperature adhesive according to claim 1, characterized in that: In the step (3), fast and slow alternating stirring is performed within the speed range of 450-750 r / min, generally stirring within the speed range of 650-750 r / min for 2-3 hours, then stirring within the speed range of 550-650 r / min for 3-4 hours, and finally stirring within the speed range of 450-550 r / min for 3-5 hours.